2019
DOI: 10.5812/msnj.97075
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Effect of Hot and Cold Massage at Spleen 6 on Pain Relief During Active Labor Phase: A Clinical Trial

Abstract: Background: Delivery is a major event that the vast majority of women experience during their lives with inevitable pain. Uncontrolled pain can prolong the labor process and cause multiple injuries to the mother and fetus. Thus, introducing measures to relieve labor pain, especially by noninvasive procedures, should be a priority in obstetrics and gynaecology.Objectives: This study aimed to compare the effect of hot and cold massage at spleen 6 (SP-6) on pain relief during active labor. Methods: This clinical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(18 citation statements)
references
References 13 publications
(19 reference statements)
0
6
0
Order By: Relevance
“…Only one study was encountered in the literature in which the effects of ice massage applied to SP6 point in reducing labor pain were examined. Nehbandani et al (2019) reported that labor pain level of the intervention group who were applied cold pressure to SP6 point was lower at minute 30 and 60 after the intervention compared to the warm massage group. 3 There are also other studies in which cold massage was applied to Hegu (LI4) point other than SP6 point.…”
Section: Discussionmentioning
confidence: 94%
See 4 more Smart Citations
“…Only one study was encountered in the literature in which the effects of ice massage applied to SP6 point in reducing labor pain were examined. Nehbandani et al (2019) reported that labor pain level of the intervention group who were applied cold pressure to SP6 point was lower at minute 30 and 60 after the intervention compared to the warm massage group. 3 There are also other studies in which cold massage was applied to Hegu (LI4) point other than SP6 point.…”
Section: Discussionmentioning
confidence: 94%
“…Managing labor pain, increasing comfort, and reducing anxiety are among the basic features of midwifery care, and they are the primary purpose of care in childbirth. [1][2][3][4][5][6] Pharmacological methods used in order to reduce labor pain have various side effects for fetal and maternal health. 3,7 Therefore, non-pharmacological methods, which have no side effects for the fetus and the mother and provide comfort, should be the primary choice in pain management.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations